2014
DOI: 10.1177/0095327x13512620
|View full text |Cite
|
Sign up to set email alerts
|

Honey I Love You, but … Investigating the Causes of the Earnings Penalty of Being a Tied-migrant Military Spouse

Abstract: Editor's note: This is the second of three articles in this issue's special section on military families. AbstractPrior empirical research on the earnings penalty of being a tied-migrant has focused primarily on the working wives of servicemen. Over the last couple of decades the increased number of women in the armed forces makes it feasible to study the earnings of another group of tied-migrants, the husbands of servicewomen. Using data from the 2000 U.S. Census, Sample Edited Detail File (SEDF), we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
(17 reference statements)
0
17
0
Order By: Relevance
“…For military wives, migration is associated with a 10% decline in employment and four-hour decline in hours worked per week; for military husbands, migration is associated with 6% employment decline and a five-hour reduction in hours worked per week (Cooke and Speirs 2005). Similarly, Hisnanick and Little (2015) found that military spousesboth men and women -experience a similar earnings gap, although the penalty is a bit sharper for women (43% for husbands and 53% for wives). Because of the demonstrated employment challenges military spouses encounter (Bradbard et al 2016;Castaneda and Harrell 2007;Hosek and Wadsworth 2013), it is expected that military spouses will be evaluated lower than comparable civilian spouses.…”
Section: Employment Challenges For Military Spousesmentioning
confidence: 95%
“…For military wives, migration is associated with a 10% decline in employment and four-hour decline in hours worked per week; for military husbands, migration is associated with 6% employment decline and a five-hour reduction in hours worked per week (Cooke and Speirs 2005). Similarly, Hisnanick and Little (2015) found that military spousesboth men and women -experience a similar earnings gap, although the penalty is a bit sharper for women (43% for husbands and 53% for wives). Because of the demonstrated employment challenges military spouses encounter (Bradbard et al 2016;Castaneda and Harrell 2007;Hosek and Wadsworth 2013), it is expected that military spouses will be evaluated lower than comparable civilian spouses.…”
Section: Employment Challenges For Military Spousesmentioning
confidence: 95%
“…Research has shown that military spouses tend to have more years of education than their civilian counterparts, yet they are generally less likely to be employed, and those who are employed tend to earn less, due in part to aspects of military life, such as frequent moves that disrupt employment, and depressed labor markets around military bases (Booth, 2003;Booth et al, 2000;Booth, Segal, and Bell, 2007;Cooney, 2003;Cooney, De Angelis, and Segal, 2011;Cooke and Speirs, 2005;Harrell et al, 2004;Heaton and Krull, 2012;Hisnanick and Little, 2014;Kniskern and Segal, 2010;Lim, Golinelli, and Cho, 2007;Little and Hisnanick, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An abundance of evidence suggests that military spouses are less likely to be employed than are their civilian counterparts, and that those who are employed earn less (Hosek et al, 2002;Harrell et al, 2004;Lim, Golinelli, and Cho, 2007;Hisnanick and Little, 2014). Some of these differences may be due to basic differences in the background and demographic characteristics between military and civilian spouses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations